The Presence of the Defense Lawyer in Vietnam’s Criminal Justice System: Substantive or Cosmetic? - Chi, Le Lan; Lan, Nguyen Thi; Ngan, Nguyen Hoang (Faculty of Law, Hasanuddin University, 2023)
Defense lawyers play an important role in protecting the rights and interests of the accused, contributing to upholding justice and reducing the number of wrongful convictions. In Vietnam, in accordance with the current Criminal Procedure Code of 2015, defense lawyers have been given more and more rights to perform legal defense activities. However, defense lawyers are still considered to be passive participants in criminal proceedings, classified under the “judicial complementary” group. The right of lawyers to collect evidence is restricted. Furthermore, other rights have not been fully implemented. The number of lawyers compared to the entire population remains low, and there are very few criminal cases that include the participation of defense lawyers. These circumstances beg the question of whether the presence of defense lawyers in Vietnam’s criminal justice system is substantive or merely a cosmetic façade intended to improve Vietnam’s global image. This paper seeks to answer this question by analyzing the results of surveys conducted with Vietnamese lawyers. Moreover, it provides some recommendations to strengthen the role of defense lawyers in the criminal justice system of Vietnam.